Simplified and standardized intrapartum management can yield high rates of successful VBAC in spontaneous labor. (18th June 2017) - Hehir, Mark P.; Mackie, Adam; Robson, Michael S.
Abstract: Objective : To examine the outcomes of vaginal birth after cesarean (VBAC) in women, in spontaneous labor, delivering after 37 weeks' gestation at an institution where trial of labor after a previous cesarean delivery (TOLAC) is encouraged and management of labor is standardized. Methods : This retrospective cohort study included 3071 women with one previous cesarean only and no vaginal delivery who underwent a trial of labor from 2001 to 2011. Women were managed using the standardized "active management of labor" intrapartum protocol. Outcomes and characteristics of women who delivered vaginally were compared with those who required cesarean delivery. Results : In spontaneous labor in their second pregnancy, those who attempted TOLAC had a 72.5% (1611/2222) rate of successful VBAC. Women who had a successful VBAC had smaller babies (3584 ± 452 g versus 3799 ± 489 g; p < 0.0001) at earlier gestations than those who had a repeat intrapartum cesarean delivery. They also required less intrapartum intervention, such as oxytocin augmentation (14.5% [234/1611] versus 41% [251/611]; p < 0.0001) and epidural anesthesia (64.8% [1044/1611] versus 82.8% [506/611]; p < 0.0001). The rate of uterine rupture was 0.54% (12/2222), while the rate of peri-partum hysterectomy was 0.18% (4/2222). Conclusion : This study shows that serious complications associated with TOLAC are rare providing intrapartum care and decision-making is made simple for the benefit of staff and patients alike. This is achieved through a standardized labor management protocol.